2016
DOI: 10.1590/1807-3107bor-2016.vol30.0065
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic abutment influences bone biomechanical behavior of immediately loaded implants

Abstract: This study aimed to evaluate the influence of the type of prosthetic abutment associated to different implant connection on bone biomechanical behavior of immediately and delayed loaded implants. Computed tomography-based finite element models comprising a mandible with a single molar implant were created with different types of prosthetic abutment (UCLA or conical), implant connection (external hexagon, EH or internal hexagon, IH), and occlusal loading (axial or oblique), for both immediately and delayed load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In general, UCLA abutments induced higher stress in crown screws than that induced by conical abutments. These results may be related to the segmented structure, which is capable to improve biomechanical behavior with the presence of two screwed connections in the conical abutment and increase the total area for stress/strain distribution and dissipation through the components (Camargos et al, 2016). These results are consistent with previous studies, which demonstrated that non-segmented abutments generate higher stress compared to segmented abutments (Ochiai et al, 2003;Aalaei et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…In general, UCLA abutments induced higher stress in crown screws than that induced by conical abutments. These results may be related to the segmented structure, which is capable to improve biomechanical behavior with the presence of two screwed connections in the conical abutment and increase the total area for stress/strain distribution and dissipation through the components (Camargos et al, 2016). These results are consistent with previous studies, which demonstrated that non-segmented abutments generate higher stress compared to segmented abutments (Ochiai et al, 2003;Aalaei et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, their use should be considered only in certain specific and indicated cases. Moreover, some studies have reported that the castable abutments present unfavorable biomechanical behavior 42 …”
Section: Discussionsupporting
confidence: 90%
“…The high risk in the screw-retained prosthesis can be related to lower preload in the screw with displacement (penetration and gaps) higher and concentrated on the threads of the screw/or abutment when compared to cement-retained (15). This difference can be even greater when use a one-piece abutment for cemented prostheses (3), since the type of abutment can influence biomechanical behavior (18). Thus, to eliminate the possibility of bias, the same abutment (UCLA casting in Co-Cr) was considered for both retention systems.…”
Section: Discussionmentioning
confidence: 99%